THE CONCEPT OF HABEAS CORPUS ACT IN REGULATING THE LEGALITY OF SUSPECTS’ DETERMINATION AS AN OBJECT OF PRETRIAL IN INDONESIA - Sinjaya, Andi; Situmeang, Janaek (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
The Habeas Corpus Act is a legal principle that protects individuals from arbitrary detention, but its implementation in the Indonesian legal system has been challenging, especially in pretrial proceedings. The regulation of suspect determination as an object of pretrial in Indonesia is debatable today, because the establishment of a suspect is not an act of coercion. This research aims to determine the concept of the Habeas Corpus Act in regulating the determination of suspects as pretrial objects. This research uses normative legal methods with statutory, conceptual, historical, and comparative approaches, and collects legal materials which are analyzed using legal theories. The results showed that pretrial was inspired by the Habeas Corpus Act. However, the regulation of suspect determination as an object of pretrial has actually deviated from the concept. Nevertheless, the Habeas Corpus Act was founded on the principle of human rights protection. Therefore, the regulation of the validity of the suspect's determination as an object of pretrial in Indonesia is consistent with the principles of the Habeas Corpus Act, which is to ensure the protection of human rights.